S‐adenosyl‐l‐methionine usage during climacteric ripening of tomato in relation to ethylene and polyamine biosynthesis and transmethylation capacity. Issue 2 (26th October 2012) - Van de Poel, Bram; Bulens, Inge; Oppermann, Yasmin; Hertog, Marten L. A. T. M.; Nicolai, Bart M.; Sauter, Margret; Geeraerd, Annemie H.
<x xml:space="preserve">Abstract</x> S‐adenosyl‐l‐methionine (SAM) is the major methyl donor in cells and it is also used for the biosynthesis of polyamines and the plant hormone ethylene. During climacteric ripening of tomato (Solanum lycopersicum 'Bonaparte'), ethylene production rises considerably which makes it an ideal object to study SAM involvement. We examined in ripening fruit how a 1‐MCP treatment affects SAM usage by the three major SAM‐associated pathways. The 1‐MCP treatment inhibited autocatalytic ethylene production but did not affect SAM levels. We also observed that 1‐(malonylamino)cyclopropane‐1‐carboxylic acid formation during ripening is ethylene dependent. SAM decarboxylase expression was also found to be upregulated by ethylene. Nonetheless polyamine content was higher in 1‐MCP‐treated fruit. This leads to the conclusion that the ethylene and polyamine pathway can operate simultaneously. We also observed a higher methylation capacity in 1‐MCP‐treated fruit. During fruit ripening substantial methylation reactions occur which are gradually inhibited by the methylation product S‐adenosyl‐l‐homocysteine (SAH). SAH accumulation is caused by a drop in adenosine kinase expression, which is not observed in 1‐MCP‐treated fruit. We can conclude that tomato fruit possesses the capability to simultaneously consume SAM during ripening to ensure a high rate of ethylene and polyamine production and transmethylation reactions. SAM usage during ripening requires a complex cellular regulation mechanism in order to control SAM levels.